Effects of airborne pollen on allergic rhinitis and asthma across different age groups in Beijing, China - Zhaobin, Sun; Yuxin, Zhao; Xingqin, An; Na, Gao; Ziming, Li; Shuwen, Zhang; Yinglin, Liang; Wenxi, Ruan; Yaqin, Bu; Jingyi, Xin; Shihong, Li (The Science of the total environment, 2024)
In the context of global warming and rapid urbanization, pollen has become a significant public health concern for Chinese citizens. However, there is a paucity of epidemiological research on the impact of pollen on allergen-linked diseases, such as allergic rhinitis and asthma, in China. Using data from the Beijing Chaoyang Hospital between 2013 and 2019, which included allergic rhinitis and asthma incidence, meteorological records, and air pollution data, we employed a Generalized Additive Model (GAM) to examine the relationship between overall and type-specific pollen concentrations in relation to varying population exposures. We found that increased overall pollen concentrations significantly increased the risks of allergic rhinitis and asthma in diverse populations. Notably, the risk of allergic rhinitis was higher than that of asthma at equivalent pollen concentrations. Seasonal trends indicated that spring pollen peaks, primarily from trees, were associated with a lower risk of both allergic rhinitis and asthma than autumn peaks, predominantly from weeds. This study underscores the importance of identifying pollen species that pose heightened risks to different demographic groups across seasons, thereby providing targeted interventions for public health agencies. [Display omitted] •Pollen concentrations have increased under global warming and are a health threat.•A generalized additive model linked pollen concentrations and rhinitis and asthma.•The source of pollen and seasonality impact pollen-linked epidemiological outcomes.•An increase in pollen concentrations increased the risk of rhinitis and asthma.•Spring pollen peaks led to a lower risk of asthma and rhinitis than autumn peaks.